2017
DOI: 10.5004/dwt.2017.20454
|View full text |Cite
|
Sign up to set email alerts
|

Tartrazine removal from water using functionalized multiwall carbon nanotubes

Abstract: a b s t r a c tThis investigation presents the advantages and limitations of tartrazine azo dye sorption on oxygen functionalized multiwalled carbon nanotubes (O-MWCNTs) synthesized by catalytic-CVD technique in LEREC laboratory, Algeria. Our adsorbent was characterized by FESEM, HR-TEM micrographs, Raman spectroscopy, ATG, XPS and specific surface area measurements (S BET ). The effects of different operational parameters like contact time, initial concentration of tartrazine, adsorbent amount, pH and tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…For this, extensive varieties of adsorbents with higher uptake ability are available to remove the dyes from wastewater, such as SBA-15/graphene oxide nanocomposites, functionalized SBA-15 [18,19] and ceramic membrane [20]. In addition, many nanomaterials with enhanced porosity and higher specific surface area such as MWNTs [19,21,22] and SBA-15/diphenyl carbazon/SDS nanocomposite [19], Zn/Al LDHs intercalated by dodecylsulfate and carbonate using hydrothermal method without calcination [23] have shown also excellent uptake ability. Synthesized starch coated magnetic nanoparticles and polymeric nanocomposites have been also used for the removal of the unspent dyes from the industrial effluents [24].…”
Section: Introductionmentioning
confidence: 99%
“…For this, extensive varieties of adsorbents with higher uptake ability are available to remove the dyes from wastewater, such as SBA-15/graphene oxide nanocomposites, functionalized SBA-15 [18,19] and ceramic membrane [20]. In addition, many nanomaterials with enhanced porosity and higher specific surface area such as MWNTs [19,21,22] and SBA-15/diphenyl carbazon/SDS nanocomposite [19], Zn/Al LDHs intercalated by dodecylsulfate and carbonate using hydrothermal method without calcination [23] have shown also excellent uptake ability. Synthesized starch coated magnetic nanoparticles and polymeric nanocomposites have been also used for the removal of the unspent dyes from the industrial effluents [24].…”
Section: Introductionmentioning
confidence: 99%
“…Nait-Merzouga et al in 2017 [ 25 ] examined the adsorption capacity of tartrazine by commercial activated carbon and an oxygen functionalized MWCNT (O-MWCNT). They modified different parameters of the adsorption process as the contact time, initial concentration of tartrazine, amount of adsorbent, pH and temperature.…”
Section: Introductionmentioning
confidence: 99%
“…They modified different parameters of the adsorption process as the contact time, initial concentration of tartrazine, amount of adsorbent, pH and temperature. They found that O-MWCNT worked better in the process of tartrazine adsorption, due to its higher specific surface area than commercial activated carbon [ 25 ].…”
Section: Introductionmentioning
confidence: 99%